-88(n-12)=2+(-89)

Simple and best practice solution for -88(n-12)=2+(-89) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -88(n-12)=2+(-89) equation:


Simplifying
-88(n + -12) = 2 + (-89)

Reorder the terms:
-88(-12 + n) = 2 + (-89)
(-12 * -88 + n * -88) = 2 + (-89)
(1056 + -88n) = 2 + (-89)
1056 + -88n = 2 + -89

Combine like terms: 2 + -89 = -87
1056 + -88n = -87

Solving
1056 + -88n = -87

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1056' to each side of the equation.
1056 + -1056 + -88n = -87 + -1056

Combine like terms: 1056 + -1056 = 0
0 + -88n = -87 + -1056
-88n = -87 + -1056

Combine like terms: -87 + -1056 = -1143
-88n = -1143

Divide each side by '-88'.
n = 12.98863636

Simplifying
n = 12.98863636

See similar equations:

| 2(2x)=3(2x+y) | | x+0.07x=25.68 | | 0.003x-.2=0.01 | | V-9.12=7.55 | | 0.0196=m^2 | | -3y=20 | | x-6.34=35.1 | | -8x-9=9x+42 | | (u-8)(u-4)= | | 9+2(5m-3)= | | 3(x-1)=x+3 | | 2n+1=-31 | | 15y^2+25y+10=0 | | 2x+3(x+4)=12 | | -6k+8=-5k | | r^3-3r^2+2=0 | | G(x)=2x^2-6x-18 | | 4x^3+6x^2-18x+18=0 | | (-12x+6)+(x-15)= | | .94(x-2)=.02(6x-3)-.02 | | 0=-157+0.05v^2 | | -4(4p+2)-12=3(2p+8) | | x+50+3x=90 | | 3(c-1)+8=14 | | 5x-55=35 | | (9x+12)-(2x+8)= | | -11r=4r+55 | | -7x(t+4)=0 | | 8t+6t-t= | | 9-1/4n=15 | | y+2=4y+1 | | 113.0=3.14r^2 |

Equations solver categories